Pengaruh Implementasi Total Quality Management (TQM) Terhadap Kepuasan Nasabah Pada Perbankan Konvensional Bank Tabungan Negara (BTN) KCP Uin Sunan Ampel Surabaya - Yosinta Damayanti (Jurnal Manajemen dan Inovasi (MANOVA), 2018)
The current era of globalization requires companies to participate in global competition. It takes an insight orscience and technology to be able to make developments for the company and its resources in order to compete.Talking about globalization cannot be separated from the banking sector. The financial sector itself plays a veryimportant role in triggering the economic growth of a region. The contribution of the banking sector cannot beseparated from the support for the world of education, especially the cooperation between universities and thebanking sector to improve service to students. One way to achieve customer satisfaction is by providing value inthe form of the application of the Total Quality Management (TQM) method. The purpose of this study was toexplain the effect of Total Quality Management (TQM) on customer satisfaction in conventional banking at theState Savings Bank, KCP UIN Sunan Ampel, Surabaya. This research uses quantitative methods withdescriptive analysis and simple linear regression as a test of influence. The results of this study state that TotalQuality Management (TQM) can significantly and positively affect Customer Satisfaction.